Developing an instrument to measure students' anti-corruption character using modern test theory - Rachmawati, Ema; Siswanto, Siswanto (Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This research aims to 1) develop an instrument construct to measure anti-corruption character (integrity), 2) test the quality of the developed integrity instrument, and 3) character profile of economics and accounting students at universities in Indonesia. This research adopts the instrument development model from Istiyono's (2020), which consists of three main stages: Planning, testing, and measurement. Each stage consists of several steps. Planning includes the preparation of objectives and the drafting of instruments and scoring guidelines. Trials and measurements were conducted on students of economics, accounting, economics education, and accounting education in 8 universities in Indonesia. The trial subjects were 200 students, and the measurement subjects were 176. The analysis proved content validity with V Aiken, construct validity with Confirmatory Factor Analysis (CFA), and reliability estimation with construct reliability. The fit of the four-category polytomous data model and student integrity was analysed with Item Response Theory (IRT). The results of this study are: 1) The integrity instrument construct consists of nine aspects, namely: a) Honesty, b) Discipline, c) Care, d) Responsibility, e) Hard work, f) Simplicity, g) Independence, h) Courage, and i) Justice, each of which consists of sub-aspects and indicators that are translated into 45 items of integrity scale statements; 2) the quality of the instrument with content validity analysis by two experts, with V-Aiken between 0.38 and 1.00. The results of the CFA analysis show that it fits with the unidimensional model and nine aspects and, based on IRT analysis, fits the Graded Response Model (GRM). Based on the information function, the instrument is suitable for almost all (integrity between -4.14 and 4.31); 3) 87% of respondents' anti-corruption character is at the very high (ST) and high (T) levels, 64% and 23% respectively. In contrast, the moderate (S), low (R) and very low (SR) levels are only 13%. As for the nine aspects of honesty and responsibility, they are low compared to the other seven aspects.